Characteristics of complex oil and oil-source correlations in heavy oil regions on the Northern Luxi uplift. (2nd May 2016) - Wu, Yinghao; Wu, Zhaohui; Xu, Shouyu; Wang, Zisong; Guo, Jinhui; Ding, Fengni
ABSTRACT: Many biomarkers are not suitable for complex types of oil at different biodegradation extent, especially multisource heavy oil in many regions. On the southern slope near Luxi Uplift, most oilfields are heavy oil regions while some are mixed heavy and light oil regions. Therefore, some parameters that can better show oil characteristics are needed to correlate complex oil and source. Many biomarkers and parameters, such as isoprene, gammacerane, Ts, Tm, diasterane, oleanane, C30 hopane, C29 sterane20S/20(R+S), and C29 steraneββ/(αα+ββ), are taken into consideration. It is found that some combinations and diagrams of some parameters have better oil-source correlation results, such as the Triangular chart of C29 S/S+R, C29 β/(β+α) and Ts/Tm, the cross plot of gammacerane/C30 hopane and Pr/Ph, the plot of C29 S/S+R and Ts/Tm, the plot of Ts/Tm and gammacerane/C30 hopane, and the plot of C29 S/S+R and C29 ββ/(ββ+ααα). Through correlations of oil and source, the oil is classified into three types, and the sources of oil in different areas are found. The oil in Boxing sag is mainly from Es3 and Es4 layers. The oil in Chunhua oilfield is mainly from Es4 . The oils in Lean, Bamian, and Wang areas are found to be derived from Es4 oil source layers in Niuzhuang Sag. To clarify oil characteristics and oil source is meaningful to compare and find the distribution of better oil types.